UNFSS Science Days Side Event: Promise of the commons for sustainable and equitable food systems - International Food Policy Research Institute; Foundation for Ecological Security; University of South Australia; Azim Premji University (International Food Policy Research Institute, 2021)
The UNFSS Dialogue on Women, Work and Food Systems identified a game-changing solution on management of commons: natural resources that are held and used collectively. The commons support food systems through direct production and provision of water, food, fuel, fodder, pollination, and other key ecosystem services, as well as important sources of resilience for communities. They thus contribute to nature-positive solutions and advance equitable livelihoods. Yet the commons are under pressure from encroachment and overuse. This side event presented evidence from a new study of the value of ecosystem services from the commons in India, as well as how strengthening governance of the commons can support equitable food systems. Harpinder Sandhu, Senior Lecturer at the University of South Australia, presented the collaborative study, followed by an overview of the FES Promise of Commons initiative by Senior Program Manager Pratiti Priyadarshini. Harini Nagendra, Director of Research Center at Azim Premji University, and Insa Theesfeld, in her capacity as the president of the International Association for the Study of the Commons, discussed the importance of safeguarding and restoring the commons and going beyond economic valuation of ecosystem services.